Evaluation Feasibility of the Yellowfin Tuna Hand Line Fishery Business in Jambula District, Ternate City (Agrikan Jurnal Agribisnis Perikanan, 2024)
The yellowfin tuna hand line fishing business in Jambula Village, Ternate City is an activity that aims to exploit yellowfin tuna fish resources with the aim of obtaining continuous profits, therefore it is necessary to carry out scientific studies related to evaluating the feasibility of the yellowfin tuna long-line fishing business in Jambula City Village. Ternate. The aim of this research is to analyze the feasibility of the yellowfin tuna hand-line fishing business in Jambula Village, Ternate City. The research was carried out in Jambula Village, Ternate City from June to November 2003. The research method used was a survey method. Data on investment costs, fixed and variable operations, fish prices, and the average number of catches per trip were obtained through interviews with owners of yellowfin tuna hand-line fishing businesses because generally the fishermen who catch them are the business owners. Considering that the number of yellowfin tuna hand-line fishermen in Jambula Subdistrict is 30, a sample of 6 (20%) fishermen respondents was taken as a representative of yellowfin tuna hand-line fishermen in that sub-district.The results of the research show that the yellowfin tuna ulura fishing business in Jambula Village, Ternate City is worth continuing and developing, with the resulting economic feasibility indicator being an average profit of IDR. 45,208,333.33/year, average net present value Rp. 254,476,531.14, average value of net benefit cost ratio 3.83, average value of internal rate of return 77.83%, average value of break event point Rp. 205,899,999.94, and the average payback period value is 1.66 years.